Levofloxacin-induced visual hallucinations: A case report and review of the literature - Valentina Raffaelli; Giulia Cantoni; Gabriella Nucera; Pietro Marino (Journal of Health and Social Sciences)
A 52-year-old female, nonalcoholic, with no significant past medical history, was empirically treated with intravenous administration of levofloxacin (LVFX, 750 mg/day) for bronchopneumonia. On day 2, she reported seeing people who are not there (visual hallucinations). She had no history of psychiatric disorders or any family history of mental illness. The patient underwent EEG and brain magnetic resonance imaging (MRI), which resulted normal. Hence, psychiatric and neurological examinations excluded delirium, encephalitis, meningitis, structural neurological lesions. Any endocrine dysfunction (e.g., hypoglyvemia, dyselectrolytemia, diabetic ketoacidosis) or toxic ingestion were also excluded. However, the possibility of levofloxacin-induced acute psychosis was considered and, on day 3, levofloxacin was discontinued with a complete resolution of the patient’s visual hallucinations by her sixth day of hospitalization. The Naranjo Probability Scale (NPS) for determining the likelihood of whether an adverse drug reaction (ADR) is actually due to the drug rather than the result of other factors was calculated as + 6 (‘probable’). In literature, the association between psychiatric adverse events and assumption of fluoroquinolones is known, but only a few cases after assumption of levofloxacin have been reported. However, the true prevalence of levofloxacininduced neuropsychiatric adverse effects could be underestimated. Therefore, physicians and psychiatrists should consider neuropsychiatric adverse effects when prescribing levofloxacin or other fluoroquinolones.